Factors affecting cognitive functioning in individuals with bipolar disorder in euthymic phase (Kerala Journal of Psychiatry, 2021)
Background: Neurocognitive studies during the euthymic phase of bipolar disorder have shown persistent cognitive deficits in 32% of patients. There is limited evidence in the Indian literature regarding this area. Neurocognitive impairment can significantly affect the overall functional recovery of these individuals. Understanding potential factors contributing to neurocognitive impairment in bipolar disorder is essential to develop prevention strategies and effective treatments. Methods: A total of 50 patients with bipolar disorder currently in euthymic phase for the last three months with a minimum duration of illness of two years and current Young Mania Rating Scale
Keywords: Bipolar disorder; cognitive impairment; euthymic; execuitive function